2011
DOI: 10.3346/jkms.2011.26.4.521
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Drug-Eluting Stents versus Bare-Metal Stents in Large Coronary Arteries in Patients with Acute Myocardial Infarction

Abstract: This study compared clinical outcomes of drug-eluting stents (DES) versus bare-metal stents (BMS) in large coronary arteries in patients with acute myocardial infarction (MI). A total of 985 patients who underwent single-vessel percutaneous coronary intervention (PCI) in large coronary arteries (≥ 3.5 mm) in lesions < 25 mm were divided into DES group (n = 841) and BMS group (n = 144). Clinical outcomes during 12 months were compared. In-hospital outcome was similar between the groups. At six months, death/MI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Lesion lengths and vessel reference diameter were visually evaluated by the operators [10-12]. And then, intravascular ultrasound (IVUS) was used to exactly estimate the target lesion and stent placement; 83.3% (50/60) of cases in group I and 69.3% (268/388) of cases in group II.…”
Section: Methodsmentioning
confidence: 99%
“…Lesion lengths and vessel reference diameter were visually evaluated by the operators [10-12]. And then, intravascular ultrasound (IVUS) was used to exactly estimate the target lesion and stent placement; 83.3% (50/60) of cases in group I and 69.3% (268/388) of cases in group II.…”
Section: Methodsmentioning
confidence: 99%
“…Sim et al compared clinical outcomes of BMS vs DES in large coronary arteries (≥3.5 mm) with lesions <25 mm in 985 AMI patients undergoing PCI (38). During 1 yr follow-up, the rates of target lesion revascularization (TLR) and target vessel revascularization (TVR) were lower in the DES group (2.5% vs 5.9%, P =0.032 and 3.1% vs 5.9%, P =0.041) than BMS group with no difference in the rate of death or MI and MACEs, suggesting usefulness of DES in large vessels in AMI patients over BMS without compromising overall safety.…”
Section: Percutaneous Coronary Interventionmentioning
confidence: 99%
“…Many studies found that the superiority of DES versus BMS decreased with increasing vessel diameter, while it increased with increasing lesion length and complexity, making the use of BMS strongly discouraged in particular in the setting of BiF and ULM. [14][15][16][17][18][19][20] Independently from site of lesions and of strategy for BiF, PF-BESs performed similar to ultrathin stents. The populations of the two registries presented also different clinical characteristics, with higher incidence of unfavorable features for PF-BES registry (older patients, higher incidence of female gender, diabetes mellitus, etc.).…”
Section: Pf-bess Have Till Now Shown Good Results For Mid and Long-termmentioning
confidence: 84%
“…After 12 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) months, rates of MACE were similar (9 vs. 8%, p = .56; see Figure 2 and Appendix web only table 7 and figure 1) without difference in TVR and TLR (3.9 vs. 2.8% and 3.0 vs. 1.7% p = . 19).…”
Section: Kind Of Ultrathin Stents Were Reported Inmentioning
confidence: 89%